A Pathway to Psychological Difficulty: Perceived Chronic Social Adversity and Its Symptomatic Reactions - Ding, Cody; Zhang, Jingqiu; Yang, Dong (Frontiers in Psychology, 2018)
In this paper, we attempt to predict and explain psychological maladjustment or difficulty. Specifically, we discuss the concept of perceived chronic social adversity, and we expect that such perceived chronic social adversity may potentially lead to chronic stress responses. Accordingly, we propose the symptomatic reactions of perceived chronic social adversity. We put forward a set of hypotheses regarding the relationships between perceived chronic social adversity and those chronic stress responses, and we further hypothesize a mediating role of individualized negative essentialism brought by perceived chronical social adversity. Resilience and individual differences in the ability to cope with perceived adversity are discussed. Future research and prevention need to pay more attention to effects of subjective personal experiences on psychological difficulty, focusing on the importance of exploring daily social experiences in improving cognitive construction processes and developing appropriate preventions.